1998
DOI: 10.1093/chemse/23.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of amiloride-sensitive sodium channels in the oral cavity of the hamster

Abstract: The distribution of amiloride-sensitive sodium channels (ASSCs) in taste buds isolated from the oral cavity of hamsters was assessed by patch clamp recording. In contrast to the case for rats, taste cells from the fungiform, foliate and vallate papillae and from the soft palate all contain functional ASSCs. The differential distribution of ASSCs between the hamster and the rat may be important for understanding the physiology underlying the differing behavioral responses of these species to sodium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…After incubation, the tongue was rinsed several times with Tyrode solution and the lingual epithelium was removed and pinned out serosal side up in a Sylgard-lined petri dish filled with Ca 2ϩ -and Mg 2ϩ -free Tyrode solution. Individual taste buds from the FF papillae were removed by gentle suction using a fire-polished pipette with a 100-to 150-m bore (25) Voltage-activated currents were recorded from individual TRCs maintained in the taste bud by using the whole cell configuration of the patch-clamp technique. Patch pipettes were pulled to a resistance of 5-10 M⍀ when filled with intracellular solution.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation, the tongue was rinsed several times with Tyrode solution and the lingual epithelium was removed and pinned out serosal side up in a Sylgard-lined petri dish filled with Ca 2ϩ -and Mg 2ϩ -free Tyrode solution. Individual taste buds from the FF papillae were removed by gentle suction using a fire-polished pipette with a 100-to 150-m bore (25) Voltage-activated currents were recorded from individual TRCs maintained in the taste bud by using the whole cell configuration of the patch-clamp technique. Patch pipettes were pulled to a resistance of 5-10 M⍀ when filled with intracellular solution.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium chloride induced activities of the chorda tympani nerve that innervates the fungiform papillae were sensitive to amiloride (Brand et al 1985;Sollars and Bernstein 1994). In marked contrast, excitement of circumvallate taste bud cells or the glossopharyngeal nerve innervating the foliate and circumvallate papillae elicited by application of NaCl and various other salts to the tongue was not suppressed by amiloride (Doolin and Gilbertson 1996;Gilbertson and Fontenot 1998;Formaker and Hill 1991;Kitada et al 1998;Ninomiya 1998). From the ion selectivity and amiloride sensitivity of the currents, it was concluded that the epithelial sodium channel ENaC mediates the Li + -and Na + -specific salty taste, whereas the amiloride-insensitive taste of Na + and other ion salts is due to different transduction pathways involving cetylpyridinium-chloride-sensitive ion channels (DeSimone et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…Following the incubation, the epithelium was incubated in Ca 2ϩ -Mg 2ϩ -free Tyrode's containing 2 mM BAPTA (Invitrogen, Eugene, OR) for 5 min. Amiloride (10 M; Sigma Chemical) was added to all solutions to help protect against enzymatic degradation of ENaCs (11). Taste buds were removed from the epithelium using a large bore (ϳ150 -200 m) pipette and plated either onto a charged microscope slide in a Tyrode's-containing Sylgard ring for patch-clamp recording or onto a Cell-Tak-coated coverslip in a laminar flow perfusion chamber for functional imaging.…”
Section: Isolation Of Taste Receptor Cellsmentioning
confidence: 99%
“…Experiments in different rodent species have shown that ENaC channels expressed in TRCs have a high sequence homology with those channels expressed in other organs. Thus, in many regards, ENaC appears similar across organ types (11,15,23,27,39).…”
mentioning
confidence: 97%